2007
DOI: 10.4314/sajas.v37i3.4091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of L-carnitine on performance, carcass and meat characteristics of quails

Abstract: The present study was conducted to determine the effects of feeding diets containing two levels of metabolizable energy (12.13 or 11.72 MJ ME/kg) and two different fat sources (sunflower-and fish-oil) with or without supplemental L-carnitine (0 or 50 mg/kg diet) on growth performance and carcass and meat characteristics of Japanese quails. Two hundred and forty day-old male quail chicks were randomly assigned to eight treatment groups, each subdivided into three replicates of 10 chicks. The chicks were raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
6
2
Order By: Relevance
“…Also, discrepant outcomes from that indicated by Al-Tamimi et al (2019), that weekly BW, BWG, FI, FCR carcass yield did not change at 5 weeks in acute heat stressed broilers for 3 hours daily which fed 1.2 g CrM /kg alone or its mixture with 1 g betaine/kg although CrM mitigated hyperthermia responses and improved the survivability. Our results are in line with those stated by Sarica et al (2007), that 50 mg/kg Car added to diet containing sunflower or fish oil as fat source with 12.13 or 11.72 MJ/kg of metabolizable energy did not affect BW, BWG, FCR and relative weights of breast, thigh drumstick, heart and gizzard of quails up to 35 days. Similarly, it was observed that 150 mg/kg Car had no influence on final BW, BWG, FCR, carcass yield and percentages of breast, wing and heart at 42 day of quails (Tufan et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Also, discrepant outcomes from that indicated by Al-Tamimi et al (2019), that weekly BW, BWG, FI, FCR carcass yield did not change at 5 weeks in acute heat stressed broilers for 3 hours daily which fed 1.2 g CrM /kg alone or its mixture with 1 g betaine/kg although CrM mitigated hyperthermia responses and improved the survivability. Our results are in line with those stated by Sarica et al (2007), that 50 mg/kg Car added to diet containing sunflower or fish oil as fat source with 12.13 or 11.72 MJ/kg of metabolizable energy did not affect BW, BWG, FCR and relative weights of breast, thigh drumstick, heart and gizzard of quails up to 35 days. Similarly, it was observed that 150 mg/kg Car had no influence on final BW, BWG, FCR, carcass yield and percentages of breast, wing and heart at 42 day of quails (Tufan et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those of Kim and Jang (2021) , who reported higher L-carnitine levels in KNBG loin meat compared to that in crossbred black goats (1.37 μmol/g) ( Kim et al, 2019 ), which were similar to those reported in beef round meat (2.64 μmol/g) ( Kim and Jang, 2021 ). L-carnitine is endogenously synthesized in organs by using lysine and methionine as precursors ( Sarica et al, 2007 ). According to previous research, alfalfa contains 6.1%–6.6% lysine and 1.8%–1.9% methionine ( Brito et al, 2014 ; Kaldy et al, 1980 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sarica et al. ( 2007 ) also reported a significant increase in sperm viability of mature male Japanese quail breeders supplemented with 250 or 500 mg L‐carnitine/kg diet. L‐carnitine supplementation also increased semen quantity and quality in broiler breeders (Golzar et al., 2007 ) and ostriches (Adabi et al., 2008 ).…”
Section: Discussionmentioning
confidence: 92%
“…Ad libitum consumption of diets containing L-carnitine at levels of 500 mg/kg (Neuman et al, 2002) or 125 mg/kg (Zhai et al, 2007) increased sperm concentration and reduced sperm lipid peroxidation in white leghorn roosters. Sarica et al (2007) also reported a significant increase in sperm viability of mature male Japanese quail breeders supplemented with 250 or 500 mg L-carnitine/kg diet. L-carnitine supplementation also increased semen quantity and quality in broiler breeders (Golzar et al, 2007) and ostriches (Adabi et al, 2008).…”
Section: Laying Performance and Reproductive Traitsmentioning
confidence: 86%